La protección de los derechos de uso de imagen de futbolistas profesionales ecuatorianos desde un Contexto de Normativa de Propiedad intelectual del Ecuador. - Burbano Flores, Eduardo David (2024)
The investigation was a documentary and legal analysis about the protection of the image rights of professional soccer players in Ecuador, from the perspective of intellectual property. In sports law there are specific regulations that address the relationships of athletes,such as the Sports Law or the Professional Soccer Player Law, which show the lack of development in certain rights that have currently become much more relevant, the rights of use stand out. of the image, and even more so when we understand them from the commercial point of view, as an economic asset of the footballers, a very vague mention of them can beevident in specific regulations and for their correct protection, it is necessary to refer to accessory laws within of Ecuadorian legislation, such as those relating to intellectual and industrial property. The general objective was to investigate the image use rights of Ecuadorian professional soccer players from a context of Ecuadorian intellectual property regulations\; in order to determine if there is a need in Ecuador to create a legal regulation ofthe rights to use the personal image of professional soccer players. This research has a qualitative approach based on both documentary analysis and interviews with experts in the subject matter under study, an exploratory level of depth, using the normativist and exegetical method, and within the conclusions it is determined that there is a need to a legalregulation in relation to the aforementioned rights, through reforms in already existing regulatory bodies in Sports Law, since due to its commercial nature, it is possible from the regulations referring to industrial and intellectual property to address the protection, negotiation and commercialization of rights in professional footballers, however, these laws,having a more general approach, cannot address certain specific aspects.